VCAM-1 expression in adult hematopoietic and nonhematopoietic cells is controlled by tissue-inductive signals and reflects their developmental origin - Ulyanova, Tatiana (The American Society of Hematology, 2005)
Although expression of vascular cell adhesion molecule 1 (VCAM-1) in endothelial cells and its functional implications have been previously appreciated, VCAM-1 expression in other than endothelial cells, especially hematopoietic cells, has been recently recognized and has not been explored in detail. Using normal mice and mice with a conditional ablation of VCAM-1 through a Tie2-driven cre transgene, we have studied the biodistribution and the pattern of VCAM-1 expression in circulating versus tissue-residing cells before and after their enforced mobilization. In the normal mouse, both at basal hematopoiesis or following mobilization, VCAM-1 expression is confined to myeloid cells residing in hematopoietic tissues, whereas free cells in circulation or in body cavities are devoid of VCAM-1 messenger RNA (mRNA) and protein. However, following culture, proliferating myeloid cells, but not lymphoid cells, express VCAM-1. In the VCAM-1–ablated mouse, there is an increase in circulating progenitors as a consequence of their ongoing release from bone marrow, a process enhanced by splenectomy. We postulate that the main mechanism leading to their release is the ablation of VCAM-1 by fibroblastic and by endothelial cells. Ablation of VCAM-1 in fibroblasts by Tie2-driven cre is a novel finding and likely denotes their developmental ancestry by Tie2-expressing (mesenchymal?) progenitor cells during development.